Musical Preferences and Criminal Behavior - Petrović, Milena Č.; Radovanović, Ivana D.; Milanković, Vera D.; Ačić, Gordana I. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The aim of this research was to examine the relationship between musical (genre) preferences and moral behaviour. The study included 216 male examinees, aged 18 to 30, divided into two groups: students (115) and prisoners serving the sentence for robbery (101). Respondents completed the Music Preferences Questionnaire designed for this study. It consists of seven questions which relate to genre preferences in different situations and emotions in everyday life, as well as genres mostly listened to in adolescence. The results of canonical discriminatory analysis and the test of the significance of differences in listening to particular genres in these situations have shown that the significant differences between groups relate to listening to classical and rock music by students and Serbian country (folk) music and alternative electro genres by prisoners, first of all during the growing up, and then out of habit and satisfaction. The results confirm the findings from the literature on the change of the status of rock music (from "rebel" into the mainstream genre), as well as the predictive value of the prevalence of early adolescent preferences for the so-called "alternative" genres.